The Contribution of Homestay Tourism to the Socio-Economic Well-Being of Rural Nepalese Communities - G.C., Ramesh (Nepalese Journal of Hospitality and Tourism Management, 2025)
This paper examines homestay tourism as a tool for socio-economic well-being in rural Nepal, focusing on the Amaltari Homestay in Nawalpur district. Data were collected from 69 respondents (62.3% male, 37.7% female) using a 5-point Likert scale survey, and reliability was assessed via Cronbach’s Alpha. Results indicate neutral to moderately positive perceptions, with mean scores near 3 for socio-economic benefits, including business opportunities (2.91), cultural preservation (2.87), and lifestyle stability (3.09). Challenges such as infrastructure gaps and limited marketing persist. The findings suggest that while homestays contribute to rural development, stronger policy support, skill training, and promotional efforts are needed to enhance their impact. The study underscores homestay tourism’s potential in fostering sustainable livelihoods and cultural preservation in Nepal’s rural communities.